Implementasi Undang – Undang No 33 Tahun 2014 Tentang Jaminan Produk Halal Kajian Teori Reflective-Law - Hakim, Riza Abdul (JATIJAJAR LAW REVIEW, 2025)
In Islamic law, Muslims are required to consume halal food and beverages including medicines in general. 80% of Indonesia's population is Muslim and the guarantee of religious freedom by the Constitution makes Law No. 33 of 2014 on Halal Product Warranty is a must. In Law No. 33 of 2014 on Halal Product Guarantee it is explained that every food, beverage, cosmetics, and medicines circulating in the community must have halal certificate. In fact, in 2017 only 110 trademarks are certified halal. Therefore, it is necessary to rematerialize Law No. 33 of 2014 on Halal Product Guarantee by make use of Indonesian Council of Ulama (MUI) as an Islamic fatwa institution in Indonesia to provide a Halal Conditional fatwa as a solution of the implementation of Law No. 33 of 2014 on Halal Product Guarantee.